Inhibitors in haemophilia B: the Italian experience. (22nd April 2013) - Castaman, G.; Bonetti, E.; Messina, M.; Morfini, M.; Rocino, A.; Scaraggi, F. A.; Tagariello, G.; ,
Summary: The prevalence of inhibitors in haemophilia B is significantly lower than that of patients with haemophilia A. However, the peculiar occurrence of allergic reactions associated with the onset of inhibitor in haemophilia B (HB) may render immune tolerance a risky procedure. We have carried out a detailed survey among all the Italian Hemophilia Centers to analyse all the patients with HB and inhibitors. A total of eight patients were reported among 282 living patients (2.8%) with severe factor IX (FIX) deficiency (FIX < 1 U dL −1 ). In addition, two deceased patients were also identified. Six patients carried nonsense mutations while in four partial or complete gene deletions were detected. Three patients (one deceased) had history of allergic/anaphylactic reaction upon substitutive treatment, which in one case was recurrent and resolved after switching to plasma derived FIX. Immune tolerance was adopted in five patients and in four complete response was achieved while in the remaining it was partial. No nephrotic syndrome was observed. Our data confirm that inhibitors in HB occur in patients with null mutations or complete/partial gene deletion. Immune tolerance can be achieved also in HB patients, without allergic reactions or nephrotic syndrome upon replacement therapy.